WD40 protein Wuho controls germline homeostasis via TRIM-NHL tumor suppressor Mei-p26 in Drosophila - Rastegari, Elham (Development, 2020)
WD40 proteins control many cellular processes via protein interactions. Drosophila Wuho (Wh, a WD40 protein) controls fertility, although the involved mechanisms are unclear. Here, we show that Wh promotion of Mei-p26 (a human TRIM32 ortholog) function maintains ovarian germ cell homeostasis. Wh and Mei-p26 are epistatically linked, with wh and mei-p26 mutants showing nearly identical phenotypes, including germline stem cell (GSC) loss, stem-cyst formation due to incomplete cytokinesis between GSCs and daughter cells, and overproliferation of GSC progeny. Mechanistically, Wh interacts with Mei-p26 in different cellular contexts to induce cell type-specific effects. In GSCs, Wh and Mei-p26 promote BMP stemness signaling for proper GSC division and maintenance. In GSC progeny, Wh and Mei-p26 silence nanos translation, downregulate a subset of microRNAs involved in germ cell differentiation and suppress ribosomal biogenesis via dMyc to limit germ cell mitosis. We also found that the human ortholog of Wh (WDR4) interacts with TRIM32 in human cells. Our results show that Wh is a regulator of Mei-p26 in Drosophila germ cells and suggest that the WD40-TRIM interaction may also control tissue homeostasis in other stem cell systems.